2010
DOI: 10.1007/s00011-010-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of caveolin-1 aggravate LPS-induced inflammatory response in AT-1 cells via up-regulation of cPLA2/p38 MAPK

Abstract: Our data demonstrated that over-expression of caveolin-1 aggravates the AT-1 injury induced by LPS, involving in modulation of the cPLA2 mediated by the cPLA2/p38 MAPK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Cav-1 −/− mice challenged with LPS showed attenuation of immune cell infiltration, microvascular leakage, and edema and had reduced LPS-induced mortality compared to controls. In lung alveolar cells, overexpression of Cav-1 aggravated LPS injury and increased the production of the TLR4-induced, pro-inflammatory cytokines, interleukin-6 (IL-6) and tumor necrosis factor alpha (TNFα) providing positive evidence that Cav-1 promotes TLR4 signaling (Lv et al, 2010). Two non-exclusive mechanisms have been proposed to describe how Cav-1 promotes TLR4 signaling in pulmonary inflammation: (1) an indirect, nitric oxide-dependent mechanism whereby eNOS hyper-activity secondary to loss Cav-1 induces nitration of TLR4 signaling components and suppression of downstream signaling (Mirza et al, 2010); (2) a direct effect whereby tyrosine phosphorylated Cav-1 interacts with TLR4 and promotes the assembly of the TLR4-MyD88 signaling complex (Jiao et al, 2013).…”
Section: Caveolins/caveolae In the Neuroretina And Rpementioning
confidence: 99%
“…Cav-1 −/− mice challenged with LPS showed attenuation of immune cell infiltration, microvascular leakage, and edema and had reduced LPS-induced mortality compared to controls. In lung alveolar cells, overexpression of Cav-1 aggravated LPS injury and increased the production of the TLR4-induced, pro-inflammatory cytokines, interleukin-6 (IL-6) and tumor necrosis factor alpha (TNFα) providing positive evidence that Cav-1 promotes TLR4 signaling (Lv et al, 2010). Two non-exclusive mechanisms have been proposed to describe how Cav-1 promotes TLR4 signaling in pulmonary inflammation: (1) an indirect, nitric oxide-dependent mechanism whereby eNOS hyper-activity secondary to loss Cav-1 induces nitration of TLR4 signaling components and suppression of downstream signaling (Mirza et al, 2010); (2) a direct effect whereby tyrosine phosphorylated Cav-1 interacts with TLR4 and promotes the assembly of the TLR4-MyD88 signaling complex (Jiao et al, 2013).…”
Section: Caveolins/caveolae In the Neuroretina And Rpementioning
confidence: 99%
“…These results further confirmed the previous studies by Garrean et al (28), which showed that cav-1 Ϫ/Ϫ mice have a reduced inflammatory response following LPS via NF-B-mediated pathways. Lv et al (61) observed that overexpression of cav-1 aggravates LPS-induced inflammation in that mouse lung alveolar type 1 cells had increased inflammatory cytokine production including IL-6 and TNF␣. Instead of using cav-1 Ϫ/Ϫ , the "gain of function" approach used in this study further endorsed the hypothesis that cav-1 mediates LPS-induced inflammation during lung injury (61,70).…”
Section: Caveolin-1 and Lung Injurymentioning
confidence: 99%
“…Lv et al (61) observed that overexpression of cav-1 aggravates LPS-induced inflammation in that mouse lung alveolar type 1 cells had increased inflammatory cytokine production including IL-6 and TNF␣. Instead of using cav-1 Ϫ/Ϫ , the "gain of function" approach used in this study further endorsed the hypothesis that cav-1 mediates LPS-induced inflammation during lung injury (61,70). Similarly, Wang and coworkers (109) first observed cav-1 expression in murine alveolar macrophages and showed that cav-1 in murine alveolar and peritoneal macrophages regulated LPSinduced proinflammatory TNF␣ and IL-6 cytokine production.…”
Section: Caveolin-1 and Lung Injurymentioning
confidence: 99%
“…Altered expression of Cav-1 has been implicated in the pathogenesis of several lung diseases (14). Cav Ϫ/Ϫ mice have thickened alveolar walls and irregular alveolar spaces with increased deposition of extracellular matrix and TGF-␤ activity, whereas overexpression of Cav-1 aggravates lipopolysaccharide (LPS)-induced inflammation and subsequent lung injury (17,29).…”
mentioning
confidence: 99%